1972
DOI: 10.1177/00220345720510023601
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Fatigue in Teeth

Abstract: This paper presents the results of experiments conducted with extracted human and bovine teeth. The teeth were subjected to thermal cycling at temperatures between 140 and 90 F. The results offer conclusive evidence that thermal fracture may be induced by the thermal stresses caused by the temperature cycling. Less than 3,000 thermal cycles cause severe cracking or the propagation of cracks previously existing in the teeth, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
6

Year Published

1984
1984
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 6 publications
1
63
0
6
Order By: Relevance
“…In addition, it is reported that bovine teeth are more susceptible to thermal fatigue and crack propagation after thermocycling than human teeth. 18) However, ultimate tensile strength and elastic modulus of bovine teeth are not significantly different from those of human teeth, 19) and bovine teeth facilitate to ensure large number of immature incisors of similar sizes. Immature permanent teeth have open and even divergent apical morphology, thin and weakened root dentin wall because of arrested tooth development.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…In addition, it is reported that bovine teeth are more susceptible to thermal fatigue and crack propagation after thermocycling than human teeth. 18) However, ultimate tensile strength and elastic modulus of bovine teeth are not significantly different from those of human teeth, 19) and bovine teeth facilitate to ensure large number of immature incisors of similar sizes. Immature permanent teeth have open and even divergent apical morphology, thin and weakened root dentin wall because of arrested tooth development.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…As suggested by Gale and Darvell, a total number of 1000 cycles of thermocycling between 5°C and 55°C was applied on the samples kept in distilled water with a stopping time of 50 seconds in each of hot and cold environments [30]. According to a study by Brown et al [31], ten cycles of thermocycling on a sample is equivalent to placing in the oral conditions for a day. Thus, 1000 cycles of thermocycling selected in this research is equivalent to putting the sample inside the patient's mouth for 100 days.…”
Section: Methodsmentioning
confidence: 99%
“…19,20 However, the number of cycles used seems to be a determining variable. 19,21 Thermal cycling exerts the same effect on cement, i.e., the difference in the coefficient of linear thermal expansion between tooth, cement and metal causes distinct movements of these substances, which in turn lead to fracture of the interlocking materials and, consequently, a reduction in tensile bond strength. Brown et al 19 (1972) showed that 3,650 cycles corresponded to one year of aging.…”
Section: Discussionmentioning
confidence: 99%